2009
DOI: 10.1027/1618-3169.56.4.283
|View full text |Cite
|
Sign up to set email alerts
|

The Brief Implicit Association Test

Abstract: The Brief Implicit Association Test (BIAT) consists of two blocks of trials with the same four categories and stimulus-response mappings as the standard IAT, but with 1/3 the number of trials. Unlike the standard IAT, the BIAT focuses the subject on just two of each block's four categories. Experiments 1 and 2 demonstrated that attitude BIATs had satisfactory validity when good (but not bad) was a focal category, and that identity IATs had satisfactory validity when self (but not other) was a focal category. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
366
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 430 publications
(385 citation statements)
references
References 23 publications
15
366
0
4
Order By: Relevance
“…To examine the effects of interventions on implicit preferences for Whites over Blacks on the MC-IAT, we modeled implicit preferences for Whites over Blacks as a function of condition. A oneway analysis of variance revealed a significant effect of condition on implicit preferences for Whites over Blacks, F(12, 1933) (Nosek et al, 2013;Sriram & Greenwald, 2009), whereas the IAT is attentive to both positive and negative associations. Using a similar procedure, Nosek and colleagues (2012) found that Bad was more strongly associated with Blacks than Whites and that this association was relatively independent of associations with Good.…”
Section: Implicit Preferences For Whites Compared To Blacks On the MCmentioning
confidence: 96%
See 1 more Smart Citation
“…To examine the effects of interventions on implicit preferences for Whites over Blacks on the MC-IAT, we modeled implicit preferences for Whites over Blacks as a function of condition. A oneway analysis of variance revealed a significant effect of condition on implicit preferences for Whites over Blacks, F(12, 1933) (Nosek et al, 2013;Sriram & Greenwald, 2009), whereas the IAT is attentive to both positive and negative associations. Using a similar procedure, Nosek and colleagues (2012) found that Bad was more strongly associated with Blacks than Whites and that this association was relatively independent of associations with Good.…”
Section: Implicit Preferences For Whites Compared To Blacks On the MCmentioning
confidence: 96%
“…We employed two implicit measures that, despite their shared reliance on categorization, have unique psychometric properties (Sriram & Greenwald, 2009;Nosek et al, 2014). We also considered using priming-based implicit measures that may capture distinct aspects of implicit racial attitudes but did not use in this research design.…”
Section: Limitationsmentioning
confidence: 99%
“…Implicit racial attitudes. Participants completed a four-block, good-focal Brief Implicit Association Test (BIAT; Sriram & Greenwald, 2009) measuring the strength of the association between the concepts "Good" and "Bad" and the categories "White people" and "Black people".…”
Section: Methodsmentioning
confidence: 99%
“…The Brief IAT (BIAT; Sriram, & Greenwald, 2009) was used as the implicit measure. Behaviorally, the critical response blocks for the task are identical to the IAT; however, perceptually, participants' attention can be focused on the category associated with good or the category associated with bad.…”
Section: Methodsmentioning
confidence: 99%
“…In order to compare good and bad associations, I needed to find a way to measure them separately. Recent theory and evidence has suggested that the Brief IAT (Sriram, & Greenwald, 2009) may be able to capture distinct "Good" and "Bad" components of evaluation (Axt and Nosek, in prep). Using these implicit measures, I investigated whether external attributions for negative events resulted in either good and bad association formation or neutralization of association formation.…”
Section: Study 3 Overviewmentioning
confidence: 99%